2004
DOI: 10.1016/j.nuclcard.2004.05.008
|View full text |Cite
|
Sign up to set email alerts
|

Do myocardial perfusion SPECT and radionuclide angiography studies in adult patients with hypertrophic cardiomyopathy have prognostic implications?

Abstract: Prognostic information from myocardial perfusion SPECT and radionuclide angiography has limited clinical significance with regard to cardiac death in adult patients with HC. However, the presence of fixed defects and lower ejection fraction in these patients has an adverse prognostic meaning for severe complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
9
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 38 publications
3
9
0
Order By: Relevance
“…This is in agreement with previous studies demonstrating that absolute resting MBF is not different among segments with differing severities of myocardial wall thickening or LGE and between epi- and endocardial myocardium [32], [33]. Romero-Farina et al showed in a myocardial perfusion SPECT study that perfusion defects at rest were associated with a higher prevalence of severe complications, indicating the prognostic relevance of resting myocardial perfusion [12]. In our study, extent of LGE and presence of T2-signal abnormalities (T2 bright and T2 dark signal) independently predicted reduced resting perfusion.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This is in agreement with previous studies demonstrating that absolute resting MBF is not different among segments with differing severities of myocardial wall thickening or LGE and between epi- and endocardial myocardium [32], [33]. Romero-Farina et al showed in a myocardial perfusion SPECT study that perfusion defects at rest were associated with a higher prevalence of severe complications, indicating the prognostic relevance of resting myocardial perfusion [12]. In our study, extent of LGE and presence of T2-signal abnormalities (T2 bright and T2 dark signal) independently predicted reduced resting perfusion.…”
Section: Discussionsupporting
confidence: 92%
“…For instance, a reduction of myocardial perfusion reserve at hyperemia or during exercise, indicating microvascular dysfunction, has frequently been described in HCM patients [12], [13], [15], [31]. Cecchi et al demonstrated its prognostic relevance in HCM: The degree of microvascular dysfunction was associated with worse prognosis and death [16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The prevalence of both reversible and fixed perfusion abnormalities is quite common and has been reported to be between 20 and 75% [43][44][45][46][47]. Data from one of the largest series consisting of 102 patients with HCM (mean age 54 AE 16 years, 56% men, 55% obstructive) reported 54% prevalence of perfusion abnormalities [46].…”
Section: Nuclear Cardiac Imaging In the Assessment Of Myocardial Ischmentioning
confidence: 99%
“…Data from one of the largest series consisting of 102 patients with HCM (mean age 54 AE 16 years, 56% men, 55% obstructive) reported 54% prevalence of perfusion abnormalities [46]. Presence and severity of perfusion abnormalities have also been shown to prognosticate subsequent impaired left ventricular systolic function [45] and unfavorable outcomes such as sudden cardiac death [46][47][48][49][50].…”
Section: Nuclear Cardiac Imaging In the Assessment Of Myocardial Ischmentioning
confidence: 99%